Analysis of Synonymous Word Collocations for Treatment and Therapy in the Covid-19 Corpus - Moh Kavin Lidinillah; Farokhah, Fiqih Aisyatul; Ikmiliansyah , Putra Irvin (JELP Journal of English Language and Pedagogy, 2023)
The world is currently infected with the covid-19 virus pandemic. The whole world is trying to find a way out, but in this case there is something positive about the covid-19 virus pandemic. One of them is learning words related to this co-19 pandemic. The purpose of this study was to identify words that were politicized with synonym words, namely treatment and therapy. The method in this study uses the corpus method with data extracted from the sketching machine application. Mother's research results are that word care is more politically related to nouns than adjectives, while therapeutic words are politicized with various words, such as nouns, adjectives, and verbs.